OPERASI ATALANTA OLEH UNI EROPA DI TELUK ADEN DALAM MENANGANI PEROMPAK SOMALIA PERIODE TAHUN 2009-2013 - Prasetyo, Hafid Dwi; Utomo, Tri Cahyo; Farabi, Nadia (Journal of International Relations, 2016)
European Union departed Operation Atalanta in the Gulf of Aden, acollective navy operation by European Union’s member countries. Theobjective of Operation Atalanta is to combat Somali piracy in the Gulf ofAden. The background of this research is based on piracy cases thathappened in the Gulf of Aden by Somali pirates. Research questions of thisresearch are why did European Union decide to launch Operation Atalantain the Gulf of Aden, and how do they manage combating Somali piracy. Inorder to answer the research questions, the paradigm of liberal institualismis applied as the theoretical framework. This framework is linked to theconcept of regional security and collective action. Through the framework,the answers are concluded that Operation Atalanta appears to be EuropeanUnion’s effort regarding the United Nations Security Council’s resolutionin combating Somali piracy. Moreover, the main mandate of OperationAtalanta is to protect the shipping of food aid from World FoodProgramme to Somalia. The main focus of this research is regarding theEuropean Union’s strategy through Operation Atalanta to combat Somalipiracy in the Gulf of Aden, and the impact given by Operation Atalanta inthe Gulf of Aden. Operation Atalanta has given a positive impact in theGulf of Aden. The number of piracy cases has declined and the situation inthe area of the Gulf of Aden has gotten more secured, and the mandates ofOperation Atalanta have been fulfilled.